THE MARKET PERFORMANCE OF BOOK BUILDING IPOs IN INDONESIA - Noni Tanjung; Yanthi Hutagaol (Journal of Applied Finance & Accounting, 2012)
This research is aimed to determine the significant difference in short run and long run performance of Initial Public Offerings (IPOs) in Indonesian Capital Market through book building or fixed price marketing method. Moreover, it is intended to distinguish the characteristics of the issuer that might influence in their choice of marketing method. The sample firms are companies who went public in year 2007 to 2010. The aftermarket performance of the IPOs is assessed based on their short run performance (initial return) and long-term performance. The model has the marketing method as the dependent variable and size, age, industry and ownership of the issuer as independent variable. The result shows there is no significance difference in the short run performance between the marketing methods. However, there are significant difference in the long-run performance. For logistic regression, there are no significant relationship between the companies’ characteristics that influence the marketing method chosen.